Ferroelectric hysteresis behavior of 0-3 PMNT-cement composites - N. Jaitanong (2018)
Lead magnesium niobate titanate (PMNT) - Portland cement (PC) composites were produced. PMNT amount used in this work was 50% by volume. The ferroelectric (P-E) hysteresis behaviors were investigated as function of both frequency and electric field for all composites. From the results, it was found that there was an increase in both the instantaneous remnant polarization (Pir) and coercive field (Eic) when the applied field increased from 5 kV/cm to 20 kV/cm, Pirwas found to increase from 1.5 to 9.8 μC/cm2and Eicwaas found to increase from 3.4 to 13.8 kV/cm. On the other hand, Pirand Eicwere found to reduce from 11.1 to 8.8 μC/cm2and from 10.8 to 15.3 kV/cm respectively, when the frequency was increased from 30-90 Hz; ascribed to the delayed response of the polarization reversal to the varying external field.